The Use of Podcasts for Listening Comprehension - Suci Partiwi (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aimed to investigate what are the effects of podcasts towards the students' listening comprehension during online learning and how are the students' perceptions of using podcasts for listening class. This study used a descriptive qualitative approach to describe the characteristic of the data. The informants in this study were one teacher of English and thirty-one students at Az-Zahrah Islamic Senior High School Palembang. Data collection techniques used interviews and questionnaires. The findings from this study are the use of podcasts for listening comprehension. The English teacher commonly teaches listening without using certain learning media. Therefore, students argued that podcast media was an accessible, helpful, and suitable medium for teaching virtual listening for eleventh-grade students at Az-Zahrah Islamic Senior High School Palembang. However, students seemed to be unfocused during the online learning because slowly internet connection became an issue and monotonous learning. Therefore, the teacher would be interested in using podcast media to attract students' attention and interests. It could also motivate them to learn virtual listening independently to improve their listening skills and comprehension.